Underwater visual census-derived fish biomass as a proxy for small-scale fisheries catch and revenue indicators - LUCA PALAZZO; ANTONIO CALÒ; ELENA DESIDERÀ; MANFREDI Di LORENZO; ANTONIO DI FRANCO; PAOLO GUIDETTI (Mediterranean Marine Science, 2026)
Empirical data about small-scale fishery indicators, such as catches and revenues, are generally scarce and scattered. In this study, we examined for the first time the relationships between fish biomass estimated through underwater visual census (UVC) and small-scale fishery indicators, namely catch per unit effort (CPUE) and revenue per unit effort (RPUE). Significant correlations could provide a practical and useful means to estimate CPUE and RPUE from UVC data, particularly in situations where fishery surveys are logistically challenging or where catch data are unavailable. Using a comprehensive dataset from 10 coastal Marine Protected Areas (MPAs) and adjacent areas across the Northern Mediterranean Sea, our results show that: i) total fish biomass of the assemblage assessed via UVC, and ii) the biomass of the most frequently recorded species in both UVC and small-scale fisheries catches (the two-banded seabream Diplodus vulgaris), are positively and significantly correlated with total CPUE and RPUE. These findings highlight that UVC-derived fish biomass data can serve to reliably estimate SSF metrics, such as CPUE and RPUE, that are key socio-ecological variables for assessing the effectiveness of MPAs. This study underscores the potential of UVC as a valuable tool for integrating ecological and socio-economic assessments in marine conservation efforts.

An ecosystem-based index for Mediterranean coralligenous reefs: A protocol to assess the quality of a complex key habitat - Patrick Astruch; Charles-François Boudouresque; Mélanie Cabral; Thomas Schohn; Enric Ballesteros; Denise Bellan-Santini; Bruno Belloni; Carlo Nike Bianchi; Olivia Cassetti; Pierre Chevaldonné; Maïa Fourt; Paolo Guidetti; et al. (Marine Pollution Bulletin, 2025)

Using Local Ecological Knowledge (LEK) to inform the multi-habitat life cycle of wreckfish: A Ligurian Sea case study for Mediterranean conservation - ELENA DESIDERÀ; DAVIDE DI BLASI; FEDERICA POLI; TREVOR J. WILLIS; SIMONE BAVA; PAOLO GUIDETTI (Mediterranean Marine Science, 2025)
Local Ecological Knowledge (LEK) from fishers and sea users is invaluable for reconstructing the occurrences of data deficient and vulnerable fish species, particularly target species. This study explores the distribution patterns of the data-deficient wreckfish Polyprion americanus in the Ligurian Sea (NW Mediterranean Sea) using semi-structured interviews with 40 sea users (27 fishers and 13 observational data providers). We identified key habitats associated with five main size classes of wreckfish, from surface waters to 1000 m depth, including vulnerable ecosystems like seamounts and cold-water coral habitats. Smaller individuals (0-1.5 kg) were mainly found in pelagic habitats, frequently near floating objects, while larger individuals (>3 kg) were common in slope and seamount habitats. Abundance declines across all size classes were attributed to overfishing and, according to some respondents, a reduction in floating debris may have specifically affected the presence of smaller individuals. Fishing techniques varied by size class, with technological advances notably impacting larger individuals near seamounts. The study supports LEK as a valuable complementary information source to conventional research, advocating for updated conservation measures, including revised size limits and enhanced protection of vulnerable habitats.

A systematic review of fishing impacts on the trophic level of fish populations and assemblages in the Mediterranean Sea - Audrey Marguin; Simona Bussotti; Paolo Guidetti; Francesca Rossi (Frontiers in Marine Science, 2025)
Fishing activities alter food web diversity and functioning. Trophic level (TL) has been used as an indicator to assess such impacts on populations and assemblages. We reviewed the scientific literature that examined the relationship between fishing and the trophic aspects of fish species and communities, by focussing on TL. We narrowed the research to the Mediterranean Sea, where fishing is an important economic income for some coastal human populations and might be jeopardised by overfishing and climate change. We collected information on the (i) geographical location; (ii) type of fisheries and (iii) the methodological approach. The 68 collected studies were geographically skewed towards the Western Mediterranean, Adriatic Sea and around Greece. Among the 45 modelling studies, 41 reported TLs for communities or catches. For the field studies, only 6 estimated TLs of species and used stable isotope analysis. Most modelling studies used data from other models, online databases or large-scale monitoring of commercial catches and research surveys, whereas the field studies collected fish locally. Only 6 field and 5 modelling studies used fishing bans or the fully protected zone of marine protected areas as no-fishing control. In these studies, TL values showed different patterns of response to fishing, probably because of differences in environmental factors. Interestingly, recent modelling studies used predictions from the model to explore the impact of different fishing pressure within global change scenarios. The use of trophodynamic modelling is powerful to describe large scale impacts and infer future scenarios, but the in situ approach, the use of stable isotopes and spatial comparisons among areas of different fishing pressure, such as no-take zones in MPA could add insights into local variations of fish TLs in response to perturbations, which might be important to refine the outcomes of the models.

Corrigendum to “Using dark diversity to disentangle the effects of protection and habitat quality on species diversity” [Biol. Conserv. 305 (May 2025) 111096] - Tal Gavriel; Ernesto Azzurro; Lisandro Benedetti-Cecchi; Iacopo Bertocci; Leda Liyue Cai; Joachim Claudet; Antonio Di Franco; Ori Frid; Paolo Guidetti; Periklis Kleitou; Demetris Kletou; Shahar Malamud; et al. (Biological Conservation, 2025)

Platelet hyperreactivity and frailty in a mouse model of Alzheimer’s disease are prevented by anti-oxidant treatment - Mauro Vismara; Silvia Maria Grazia Trivigno; Marta Zarà; Stefania Momi; Paolo Gresele; Marina Camera; Ilaria Canobbio; Gianni Francesco Guidetti; Mauro Torti (GeroScience, 2025)
Frailty is an age-related syndrome commonly associated with different comorbidities, and its occurrence is particularly frequent in patients with Alzheimer’s disease (AD). A persisting low-grade inflammation has been suggested to favor the onset of both AD and frailty. Besides their role in hemostasis and thrombosis, blood platelets are true inflammatory cells, and their direct contribution to the onset and progression of AD has been documented. In this work, we investigated whether platelet hyperreactivity and pro-oxidative functions are implicated in the development of frailty in a mouse model of AD, the APP23 mice. Assessment of 31 specific clinical signs of deterioration in mice at 3, 9, and 18 months of age demonstrated that the development of frailty was significantly more pronounced in the APP23 mice compared to wild-type littermates. In 18-month-old APP23 mice, a significant platelet hyperreactivity was detected as shown by a significantly stronger platelet aggregation in response to submaximal stimulation of both collagen and thrombin receptors. Moreover, the pro-inflammatory function of platelets, evaluated as circulating and agonist-induced platelet-neutrophil aggregate formation, was significantly increased in aged APP23 mice compared to wild-type littermates. Platelet hyperreactivity was partially prevented by prolonged treatment with the anti-oxidant agent Tempol, which reduced both agonist-induced aggregation and platelet-neutrophil aggregate formation. Importantly, prolonged treatment of APP23 mice with Tempol significantly reduced also the frailty index score in 18-month-old animals. These results outline the possible beneficial effect of an anti-oxidant treatment in hampering platelet hyperreactivity and preventing the onset of frailty associated to AD.

Pre-Lessepsian isotopic niche spaces: using paleoecological proxies to assess the impact of ongoing bioinvasions on fishes in the eastern Mediterranean Sea - RACHEL M. WINTER; ELENA DESIDERÁ; PAOLO GUIDETTI; MATTHEW VON TERSCH; MICHAEL DEE; MICHELLE ALEXANDER; CANAN ÇAKIRLAR (Mediterranean Marine Science, 2025)
Ongoing bioinvasions of Lessepsian species via the Suez Canal have profoundly altered marine coastal ecosystems in the eastern Mediterranean. In response to these Lessepsian migrations, some indigenous fishes have been observed to have widened their trophic niches and diversified their foraging strategies. Effects of invasive taxa are further compounded by modern anthropogenic drivers such as overfishing, habitat degradation, and pollution. The scale and characteristics of these recent changes in trophodynamics for broader ichthyofaunal communities are poorly understood due to a lack of data predating Lessepsian migrations; paleoecological data is, therefore, essential. Here, we present a substantial body of new carbon (δ13C) and nitrogen (δ15N) isotopic data from Middle to Late Holocene archaeological fish collagen (n=137), combined with previously published results (n=44) to establish paleoecological baselines for the region. An emphasis is placed on groupers (Epinephelidae) due to their high ubiquity in Mediterranean archaeological contexts and importance to rocky reef ecosystems today. We demonstrate that modern, indigenous Mediterranean fish have expanded their trophic niches beyond their pre Lessepsian migrations baseline foraging ecology. Paleo data further show that fishes in middle and lower trophic levels have the highest degree of overlap in isotopic niche spaces, suggesting greater levels of competition for trophic resources. Our study highlights the importance of integrating data from historical ecological baselines into our assessments of bioinvasions and, more broadly, anthropogenically driven ecosystem alterations.

A peculiar coral formation in the Mediterranean Sea, and its associated biota - Roberto Arrigoni; Elena Desiderà; Simone Bava; Carla Morri; Carlo Nike Bianchi; Paolo Guidetti (Ecology, 2025)

Using dark diversity to disentangle the effects of protection and habitat quality on species diversity - Tal Gavriel; Ernesto Azzurro; Lisandro Benedetti-Cecchi; Iacopo Bertocci; Leda Liyue Cai; Joachim Claudet; Antonio Di Franco; Ori Frid; Paolo Guidetti; Periklis Kleitou; Demetris Kletou; Shahar Malamud; et al. (Biological Conservation, 2025)

Access and well-being in small-scale fisheries - Nathan J. Bennett; Antonio Calò; Paolo Guidetti; Marco Milazzo; Giulia Prato; Emna Ben Lamine; Claudia Scianna; Antonio Di Franco (Marine Policy, 2024)

Fully protected marine areas linked to reduced home ranges of fishes - Sarah Ohayon; David Abecasis; Pedro R. Almeida; Josep Alós; Eneko Aspillaga; Ana Filipa Belo; José Lino Costa; Antonio Di Franco; Manfredi Di Lorenzo; Adrian Ferguson; Paolo Guidetti; Sebastian Kraft; et al. (Fish and Fisheries, 2024)
Home range size is a fundamental trait that can affect the probability of fish being harvested and, at the same time, may be affected by fishing. The relationship between home range size and fishing will impact the effectiveness of fully protected areas (FPAs), as it will influence the number of fish moving into fished areas, affecting both spillover and edge effects. One hypothesis is that individuals within FPAs will present reduced home range size relative to individuals in fished areas. This pattern can be driven by demographic selection (e.g. fishing of individuals with large home ranges leaving the FPAs), improved habitat requiring less foraging movements, or behavioural changes associated with reduced fishing threats. To test the relationship between home range size and protection, we compiled 1143 individual‐level home range sizes based on acoustic tracking, covering 17 species from 11 FPAs in 7 countries, with information on distance from FPA borders. A dichotomic analysis (in/out of FPAs) did not support a significant change in the home range size between FPAs and fished areas. However, continuous analysis across the FPA borders demonstrated reduced home range size within the FPAs. We did not find an effect of FPA age or size on this pattern. While we cannot pinpoint the underlying mechanism for the pattern revealed, we suggest behavioural changes as the main driver for reduced home range within FPAs. This mechanism will lead to more resident populations within FPAs, reducing fishing mortality within FPAs yet limiting spillover benefits to adjacent fisheries.

The Northernmost Records of Caranx crysos (Osteichthyes: Carangidae) in the NW Mediterranean Sea - Davide Di Blasi; Simone Bava; Elena Desiderà; Lorenzo Merotto; Federica Poli; Paolo Guidetti (Thalassas: An International Journal of Marine Sciences, 2024)

Social-ecological features of set nets small-scale fisheries in the context of Mediterranean marine protected areas - ANTONIO CALÒ; ANTONIO DI FRANCO; CHARALAMPOS DIMITRIADIS; LEA PIACENTINI; PATRICIA VENTURA; ALEXIS PEY; JOSÉ ANTONIO GARCÍA-CHARTON; ERIC CHARBONNEL; VICTOR DECUGIS; FRANCESCO DE FRANCO; IVONI FOURNARI-KONSTANTINIDOU; JOSIPA GRBIN; et al. (Mediterranean Marine Science, 2023)
The small-scale fisheries (SSF) sector has attracted considerable attention over the last decade due to its major importance in sustaining the livelihoods of coastal communities worldwide, poverty alleviation, food security, social wealth and traditions. Despite this importance, quantitative and qualitative information on SSF is still largely lacking and when available, it tends to be scattered or very localized. SSF are also among the very few professional extractive activities generally allowed within Marine Protected Areas (MPAs), and are therefore expected to acquire further momentum in the near future in light of the projected increase of protected marine surface area due to international commitments. However, SSF associated with areas including MPAs may differ from those operating in unprotected contexts with regard to a range of socio-ecological aspects, thus potentially making management strategies currently in force unsuitable, and requiring the development of ad hoc local and regional policies. Here, we assessed the socio-ecological dimension of SSF operating within and around 11 Mediterranean MPAs, in six EU countries, with the aim of identifying relevant patterns that could inform policy and management relative to this fishing sector in view of the forthcoming increase of the marine surface area under protection. To do so, we have adopted a collaborative approach with fishers and combined a photo-sampling survey of 1,292 set net (mainly trammel-nets) fishing operations at landing with 149 semi-structured interviews with fishers, to gather information on features and catches of SSF fleets (e.g. vessel characteristics, gears, catch composition, catch and revenue per unit of effort). Overall, results highlighted: 1) multiple shared features emerging at regional level (i.e. among the 11 study areas), such as the predominant use of set nets, the major contribution of a limited number of species to the overall catch and revenue, the occurrence in the catch of threatened species and/or undersized individuals; 2) a variety of distinctive socio-ecological features differentiating local SSF communities such as the species mainly contributing to catch and revenue, species size distribution and fleet characteristics. In addition to presenting elements to inform common policies and strategies for SSF management in the context of MPAs, our study provides guidance for the development of a standard methodology for the full documentation of SSF in the Mediterranean Sea.

Climate change impacts on Mediterranean fisheries: A sensitivity and vulnerability analysis for main commercial species - Shekoofeh Farahmand; Nathalie Hilmi; Mine Cinar; Alain Safa; Vicky W.Y. Lam; Salpie Djoundourian; Wassim Shahin; Emna Ben Lamine; Alexandre Schickele; Paolo Guidetti; Denis Allemand; Virginie Raybaud (Ecological Economics, 2023)

Redistribution of fisheries catch potential in Mediterranean and North European waters under climate change scenarios - Emna Ben Lamine; Alexandre Schickele; Paolo Guidetti; Denis Allemand; Nathalie Hilmi; Virginie Raybaud (Science of The Total Environment, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Multiple indices on different habitats and descriptors provide consistent assessments of environmental quality in a marine protected area - Alice Oprandi; Fabrizio Atzori; Annalisa Azzola; Carlo Nike Bianchi; Nicoletta Cadoni; Lara Carosso; Elena Desiderà; Francesca Frau; Maria Leonor Garcia Gutiérrez; Paolo Guidetti; Carla Morri; Luigi Piazzi; et al. (Frontiers in Marine Science, 2023)
In the last decades, climate change and human pressures have increasingly and dramatically impacted the ocean worldwide, calling for urgent actions to safeguard coastal marine ecosystems. The European Commission, in particular, has set ambitious targets for member states with two major directives, the Water Framework Directive (WFD) and the Marine Strategy Framework Directive (MSFD), both designed to protect the marine environment in EU waters. Diverse biotic indices have accordingly been developed to assess water and habitat quality. The WFD adopts four Biological Quality Elements (BQEs), whereas the MSFD recommends a set of eleven qualitative descriptors. The borderline between water quality and habitat quality is hard to trace and so far most assessments have involved the use of a few indices and were mainly related to a single BQE or qualitative descriptor. In this study, thanks to the availability of a large dataset encompassing a wide array of descriptors, we compared the performance of 11 biotic indices relative to three habitats/biotic components (reefs, seagrass, and fish) of the Marine Protected Area (MPA) of Capo Carbonara (SE Sardinia, Italy). The aim was to assess whether the indices were consistent in defining the environmental status in the MPA investigated. We used the graphical approach RESQUE (REsilience and QUality of Ecosystem), which enabled us to obtain a single and comprehensive measure of the status of the environment by integrating several metrics. This approach was applied here to different habitats for the first time. All indices were consistent with each other in confirming the good status of Capo Carbonara MPA. The use of RESQUE provided insights to interpret the differences between water quality, defined according to the WFD, and habitat quality, defined according to the MSFD. Differences between the two EU directives, in terms of either requirements or goals, have long been discussed but the present study highlights for the first time that they are congruent in their assessment of the environmental status of marine ecosystems.

Multi‐specific small‐scale fisheries rely on few, locally essential, species: Evidence from a multi‐area study in the Mediterranean - Antonio Calò; Antonio Di Franco; Federico Quattrocchi; Charalampos Dimitriadis; Patricia Ventura; Marco Milazzo; Paolo Guidetti (Fish and Fisheries, 2022)
Achieving sound management of small‐scale fisheries (SSFs) is globally recognized a key priority for sustaining livelihoods, local economies, social wealth and cultural heritage in coastal areas. The paucity of information on SSFs often prevents the proper assessment of different socio‐ecological aspects, potentially leading to draw inappropriate conclusions and hampering the development and adoption of effective policies to foster SSF sustainability. To respond to the growing global call to assess these fisheries, we carried out a multi‐disciplinary and data‐rich assessment of SSFs at 11 areas in 6 Mediterranean EU countries, combining the analysis of 1292 SSF fishing operations and 149 semi‐structured surveys of fishers. Specifically, we aimed at assessing (1) landed species contribution to SSF catches and revenues and (2) the spatial variability in a set of fishery socio‐ecological descriptors. Results highlighted that, in spite of a high species diversity, Mediterranean SSFs actually rely economically upon a very limited number of species with catch and revenues per unit of effort mostly determined by less than 5 species, that can guarantee high and stable catches and revenues over time. Moreover, some fishing communities were found to rely on a restricted number of gears. These evidences suggest, that some SSFs' properties often assumed, but never broadly verified, should be carefully reconsidered, especially when viewed from a broader socio‐ecological perspective, as in the case of the diversified portfolio or of the polyvalence of fishing gears. Taking the local scale into proper account is likely to reduce the risk of implementing management strategies potentially generating socio‐ecological inequalities.

Improving predictions of invasive fish ranges combining functional and ecological traits with environmental suitability under climate change scenarios - Alexandre Schickele; Paolo Guidetti; Sylvaine Giakoumi; Argyro Zenetos; Patrice Francour; Virginie Raybaud (Global Change Biology, 2021)
Biological invasions represent one of the main threats to marine biodiversity. From a conservation perspective, especially in the context of increasing sea warming, it is critical to examine the suitability potential of geographical areas for the arrival of Range‐Expanding Introduced and Native Species (REINS), and hence anticipate the risk of such species to become invasive in their new distribution areas. Here, we developed an empirical index, based on functional and bio‐ecological traits, that estimates the Invasive Potential (IP; i.e. the potential success in transport, introduction and population establishment) for a set of 13 fishes that are expanding their distributional range into the Mediterranean Sea, the most invaded sea in the world. The IP index showed significant correlation with the observed spreading of REINS. For the six species characterized by the highest IP, we calculated contemporary and future projections of their Environmental Suitability Index (ESI). By using an ensemble modelling approach, we estimated the geographical areas that are likely to be the most impacted by REINS spreading under climate change. Our results demonstrated the importance of functional traits related to reproduction for determining high invasion potential. For most species, we found high contemporary ESI values in the South‐eastern Mediterranean Sea and low to intermediate contemporary ESI values in the Adriatic Sea and North‐western Mediterranean sector. Moreover, we highlighted a major potential future expansion of high ESI values, and thus REINS IP, towards the northern Mediterranean, especially in the northern Adriatic Sea. This potential future northward expansion highlights the risk associated with climate‐induced impacts on ecosystem conservation and fish stock management throughout the entire Mediterranean Sea.

Otolith chemical composition suggests local populations of Antarctic silverfish Pleuragramma antarctica (Boulenger, 1902) around Antarctica are exposed to similar environmental conditions at early life stages - Antonio Di Franco; Antonio Calò; Giuseppe Egidio De Benedetto; Laura Ghigliotti; Antonio Pennetta; Mathieu D. M. Renard; Eva Pisano; Marino Vacchi; Paolo Guidetti (Polar Biology, 2021)

Using complementary visual approaches to investigate residency, site fidelity and movement patterns of the dusky grouper (Epinephelus marginatus) in a Mediterranean marine protected area - Elena Desiderà; Egidio Trainito; Augusto Navone; Rémi Blandin; Luana Magnani; Pieraugusto Panzalis; Carlotta Mazzoldi; Paolo Guidetti (Marine Biology, 2021)
Assessing individuals’ abundance, residency (presence at a site within a certain period) and site fidelity (tendency to return to the same site in subsequent seasons or years) is crucial for evaluating and improving the effectiveness of spatial conservation/management measures regarding ecologically and socio-economically valuable species. Using underwater visual census (UVC) and photo-identification (photo-ID) techniques, we estimated the abundance, residency and site fidelity of the dusky grouper, Epinephelus marginatus , at two protected sites within the Tavolara-Punta Coda Cavallo Marine Protected Area (Sardinia, Italy) in the summers of 2017–2018. The scope and spatio-temporal resolution of the study was extended by involving volunteer recreational divers in the photo collection. Grouper mean densities varied significantly across sampling dates, with a significant variability between the 2 years and the two investigated sites. At least 94 grouper visited the study sites in the summers of 2017–2018 based on the analysis of 968 high-quality photos using a semi-automated software to photo-identify individuals. Overall, the most frequently sighted grouper was recorded on 32 different days and 21 individuals (22%) identified in 2017 were re-sighted in 2018. The participation of volunteer recreational divers helped detect the inter-site (3.5–4 km apart) movements of a female and a male, supporting previous findings regarding the occurrence of reproduction-related movements. This study provides novel insights into the residency and site-fidelity patterns of the dusky grouper, and its small-scale movements probably related to reproduction. Specifically, we provide indications that effective protection from fishing should encompass the entire area used by grouper for reproductive movements.

Environmental DNA effectively captures functional diversity of coastal fish communities - Giorgio Aglieri; Charles Baillie; Stefano Mariani; Carlo Cattano; Antonio Calò; Gabriele Turco; Davide Spatafora; Antonio Di Franco; Manfredi Di Lorenzo; Paolo Guidetti; Marco Milazzo (Molecular Ecology, 2021)
Robust assessments of taxonomic and functional diversity are essential components of research programmes aimed at understanding current biodiversity patterns and forecasting trajectories of ecological changes. Yet, evaluating marine biodiversity along its dimensions is challenging and dependent on the power and accuracy of the available data collection methods. Here we combine three traditional survey methodologies (underwater visual census strip transects [UVCt], baited underwater videos [BUV] and small‐scale fishery catches [SSFc]), and one novel molecular technique (environmental DNA metabarcoding [eDNA]—12S rRNA and cytochrome oxidase subunit 1 [COI]) to investigate their efficiency and complementarity in assessing fish diversity. We analysed 1,716 multimethod replicates at a basin scale to measure the taxonomic and functional diversity of Mediterranean fish assemblages. Taxonomic identities were investigated at species, genus and family levels. Functional identities were assessed using combinations of morphological, behavioural and trophic traits. We show that: (a) SSFc provided the higher taxonomic diversity estimates followed by eDNA, and then UVCt and BUV; (b) eDNA was the only method able to gather the whole spectrum of considered functional traits, showing the most functionally diversified and least redundant fish assemblages; and (c) the effectiveness of eDNA in describing functional structure reflected its lack of selectivity towards any considered functional trait. Our findings suggest that the reach of eDNA analysis stretches beyond taxon detection efficiency and provides new insights into the potential of metabarcoding in ecological studies.

Assessing spillover from marine protected areas and its drivers: A meta‐analytical approach - Manfredi Di Lorenzo; Paolo Guidetti; Antonio Di Franco; Antonio Calò; Joachim Claudet (Fish and Fisheries, 2020)
Overfishing may seriously impact fish populations and ecosystems. Marine protected areas (MPAs) are key tools for biodiversity conservation and fisheries management, yet the fisheries benefits remain debateable. Many MPAs include a fully protected area (FPA), restricting all activities, within a partially protected area (PPA) where potentially sustainable activities are permitted. An effective tool for biodiversity conservation, FPAs, can sustain local fisheries via spillover, that is the outward export of individuals from FPAs. Spillover refers to both: “ecological spillover”: outward net emigration of juveniles, subadults and/or adults from the FPA; and “fishery spillover”: the fraction of ecological spillover that directly benefits fishery yields and revenues through fishable biomass. Yet, how common is spillover remains controversial. We present a meta‐analysis of a unique global database covering 23 FPAs worldwide, using published literature and purposely collected field data, to assess the capacity of FPAs to export biomass and whether this response was mediated by specific FPA features (e.g. size, age) or species characteristics (e.g. mobility, economic value). Results show fish biomass and abundance outside FPAs was higher: (a) in locations close to FPA borders ( 200 m); (b) for species with a high commercial value; and (c) in the presence of PPA surrounding the FPA. Spillover was slightly higher in FPAs that were larger and older and for more mobile species. Based on the broadest data set compiled to date on marine species ecological spillover beyond FPAs' borders, our work highlights elements that could guide strategies to enhance local fishery management using MPAs.

First direct evidence of reproductive behaviour of the white grouper, Epinephelus aeneus (Geoffroy Saint-Hilaire, 1817) - ELENA DESIDERÀ; LUANA MAGNANI; AUGUSTO NAVONE; PAOLO GUIDETTI; CARLOTTA MAZZOLDI (Mediterranean Marine Science, 2019)
This study describes the first ever reported direct observation of a pair spawning event and the reproductive liveries of the white grouper, Epinephelus aeneus. Spawning took place on a rocky bank located in the Marine Protected Area (MPA) of Tavolara-Punta Coda Cavallo (NE Sardinia, Italy), in the Western Mediterranean Sea. In the evening of August 4th, 2018, the spawning of two large-sized individuals (~90 cm total length), displaying distinct colour patterns, was observed using SCUBA diving. This direct observation is the first record of E. aeneus male reproductive livery, characterized by a darker coloration on the head, the dorsal part of the body and the caudal fin. In addition, information on the environmental conditions in which reproduction occurred was collected. At the study site, relatively high seawater temperatures were recorded at the time of the E. aeneus spawning (24 °C at 24.7 m), as well as over the 2018 summer months (July-September), even in deep waters (>35 m), compared to previous summers. The spawning event occurred in a coralligenous-dominated seascape where fishing is prohibited, while diving activities are allowed. The site hosts abundant populations of ecologically and commercially valuable fish species (e.g., groupers, sparid fishes), with significant proportions of large-sized individuals (i.e. reproducers). Further studies are needed to advance our knowledge of the white grouper, with a particular emphasis on reproduction and the importance of implementing effective protection measures. Prioritizing management actions at key reproductive sites, such as rocky banks, is essential for ensuring the protection and/or recovery of over-exploited species.

Dual-phase 16 slice CT angiography in stroke imaging: a poor man’s multiphase study? - Nicola Morelli; Eugenia Rota; Paolo Immovilli; Giuseppe Marchesi; Donata Guidetti; Emanuele Michieletti; John Morelli (Acta Neurologica Belgica, 2019)

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Fish assemblages along the coasts of Tunisia: a baseline study to assess the effectiveness of future Marine Protected Areas - EMNA BEN LAMINE; PAOLO GUIDETTI; MOHAMED SALAH ROMDHANE; PATRICE FRANCOUR (Mediterranean Marine Science, 2018)
The present study investigated coastal fish assemblages, using Underwater Visual Census (UVC) transects, in Tunisia (south Mediterranean basin). The rationale behind this work is to get i) a suggestive evidence about the status of fish assemblages, and ii) baseline data at 3 locations in Tunisia where 3 MPAs will be established, before the implementation of protection measures. At each location, we used a sampling design where fish censuses were performed in two types of zone: zones that will be inside MPAs, and zones that will remain outside. On the whole, 49 taxa belonging to 19 families were censused. Data reveal clear symptoms of overfishing, especially in terms of dominance of small- and medium-sized individuals of commercially relevant species. Our analyses, moreover, did not show any significant difference in whole fish assemblage structures (considering both density and biomass), patterns of average species richness, total fish density and biomass, density and biomass of different trophic categories of fishes, size distribution of commercially relevant species, between future-protected and unprotected zones. Overall, results suggest that 1) current fish assemblages at the three studied locations are likely to be seriously impacted by fishing activities, and 2) these data could be used as reliable baselines to assess the effectiveness of protection measures within the MPAs that will be established in the future. Our study is the first in Tunisia, and in North African coasts, that assessed distribution patterns of coastal fish assemblages by means of UVC, using a formal spatially replicated sampling design for resource management.

Distribution patterns of the cardinal fish Apogon imberbis (Linnaeus, 1758) within Mediterranean marine caves and its potential role for cave ecosystem functioning - Bussotti Simona; Di Franco Antonio; Pey Alexis; Vieux Jean-Vincent; Planes Serges; Guidetti Paolo (Frontiers in Marine Science, 2016)

Towards a framework for assessment and management of cumulative human impacts on marine food webs - Sylvaine Giakoumi; Benjamin S. Halpern; Loïc N. Michel; Sylvie Gobert; Maria Sini; Charles‐François Boudouresque; Maria‐Cristina Gambi; Stelios Katsanevakis; Pierre Lejeune; Monica Montefalcone; Gerard Pergent; Christine Pergent‐Martini; et al. (Conservation Biology, 2015)
Effective ecosystem‐based management requires understanding ecosystem responses to multiple human threats, rather than focusing on single threats. To understand ecosystem responses to anthropogenic threats holistically, it is necessary to know how threats affect different components within ecosystems and ultimately alter ecosystem functioning. We used a case study of a Mediterranean seagrass (Posidonia oceanica) food web and expert knowledge elicitation in an application of the initial steps of a framework for assessment of cumulative human impacts on food webs. We produced a conceptual seagrass food web model, determined the main trophic relationships, identified the main threats to the food web components, and assessed the components’ vulnerability to those threats. Some threats had high (e.g., coastal infrastructure) or low impacts (e.g., agricultural runoff) on all food web components, whereas others (e.g., introduced carnivores) had very different impacts on each component. Partitioning the ecosystem into its components enabled us to identify threats previously overlooked and to reevaluate the importance of threats commonly perceived as major. By incorporating this understanding of system vulnerability with data on changes in the state of each threat (e.g., decreasing domestic pollution and increasing fishing) into a food web model, managers may be better able to estimate and predict cumulative human impacts on ecosystems and to prioritize conservation actions.

Effects of tadalafil administration on plasma markers of exercise-induced muscle damage, IL6 and antioxidant status capacity - Roberta Ceci; Guglielmo Duranti; Paolo Sgrò; Massimiliano Sansone; Laura Guidetti; Carlo Baldari; Stefania Sabatini; Luigi Di Luigi (European Journal of Applied Physiology, 2015)

Comanagement Practices Enhance Fisheries in Marine Protected Areas - PAOLO GUIDETTI; JOACHIM CLAUDET (Conservation Biology, 2010)
Fishing activities worldwide have dramatically affected marine fish stocks and ecosystems. Marine protected areas (MPAs) with no‐take zones may enhance fisheries, but empirical evidence of this is scant. We conducted a 4‐year survey of fish catches around and within an MPA that was previously fully closed to fishing and then partially reopened under regulated comanaged fishing. In collaboration with the fishers and the MPA authority, we set the fishing effort and selected the gear to limit fishing impact on key fish predators, juvenile fish stage, and benthic communities and habitats. Within an adaptive comanagement framework, fishers agreed to reduce fishing effort if symptoms of overfishing were detected. We analyzed the temporal trends of catch per unit of effort (CPUE) of the whole species assemblages and CPUE of the four most valuable and frequent species observed inside the opened buffer zone and outside the MPA investigated. After the comanaged opening, CPUE first declined and then stabilized at levels more than twice that of catches obtained outside the MPA. Our results suggest that working closely with fishers can result in greater fisheries catches. Partial protection of coastal areas together with adaptive comanagement involving fishers, scientists, and managers can effectively achieve conservation and fishery management goals and benefit fishing communities and alleviate overfishing.

Predator diversity and density affect levels of predation upon strongly interactive species in temperate rocky reefs - Paolo Guidetti (Oecologia, 2007)

An improved method to compute the solute and water derangements of hyperglycaemia - Ettore Bartoli; Luca Bergamasco; Pier Paolo Sainaghi; Francesca Guidetti; Luigi Castello (European Journal of Applied Physiology, 2007)

Potential of Marine Reserves to Cause Community‐Wide Changes beyond Their Boundaries - PAOLO GUIDETTI (Conservation Biology, 2007)
Fishing and other human activities can alter the abundances, size structure, and behavior of species playing key roles in shaping marine communities (e.g., keystone predators), which may in turn cause ecosystem shifts. Despite extensive evidence that cascading trophic interactions can underlie community‐wide recovery inside no‐take marine reserves by protecting high‐level predators, the spatial extent of these effects into adjacent fished areas is unknown. I examined the potential for community‐wide changes (i.e., the transition from overgrazed coralline barrens to macroalgal beds) in temperate rocky reefs within and around a no‐take marine reserve. For this purpose I assessed distribution patterns of predatory fishes, sea urchins, and barrens across the reserve boundaries. Predatory fishes were significantly more abundant within the reserve than in adjacent locations, with moderate spillover across the reserve edges. In contrast, community‐wide changes of benthic assemblages were apparent well beyond the reserve boundaries, which is consistent with temporary movements of predatory fishes (e.g., foraging migration) from the reserve to surrounding areas. My results suggest that no‐take marine reserves can promote community‐wide changes beyond their boundaries.

Effects of Desertification Caused by Lithophaga lithophaga (Mollusca) Fishery on Littoral Fish Assemblages along Rocky Coasts of Southeastern Italy - PAOLO GUIDETTI; SIMONETTA FRASCHETTI; ANTONIO TERLIZZI; FERDINANDO BOERO (Conservation Biology, 2004)
We surveyed shallow, rocky reefs in southwestern Apulia (Mediterranean Sea) to assess the effects on coastal fish assemblages of the date mussel ( Lithophaga lithophaga ) fishery, an illegal practice that strips the rocky reef bare. We visually sampled fish four times over 15 months at three locations, one affected by date‐mussel fishery and two controls. The fish assemblage at the affected location differed significantly from those at the control locations over all sampling times. Herbivorous fishes, sparids, and labrids (genus Symphodus ) contributed most to the differences between the affected location and controls. Lower densities of Symphodus spp. were observed at the affected location, whereas detritivorous fishes were recorded exclusively at control sites. Small serranids and sparids showed temporal trends that differed between the affected location and the control locations. Our results suggest that the date‐mussel fishery affects fish assemblages chiefly through reduction of arborescent macroalgae (contributing to habitat complexity and primary production) and emphasize the need for more effective policing against this destructive practice.

Fish Assemblages in Shallow Marine Caves of the Salento Peninsula (Southern Apulia, SE Italy) - Simona Bussotti; Francesco Denitto; Paolo Guidetti; Genuario Belmonte (Marine Ecology, 2002)
Fish assemblages of three shallow marine caves from the Salento Peninsula (Apulia, SE Italy) were investigated in July 2000. Data were collected in situ by using visual census. A total of nineteen fish species were recorded inside the caves. The species richness generally displayed a similar pattern in all three caves, decreasing from the entrance towards the innermost sections, whereas the patterns of total fish abundance differed among caves. Apogon imberbis (mainly represented by juveniles) was the most important species in terms of number of individuals (accounting for more than 85% of the censused fish) and showed a fairly even distribution inside the investigated caves. Without the numerical contribution of A. imberbis , fish abundance decreased from the entrance to the inner sections and this pattern was common to all three caves. Juvenile fishes of economic interest ( e. g., Diplodus vulgaris and Epinephelus marginatus ) were also recorded inside. The present study suggests that: (1) environmental constraints could affect distribution patterns in fish species richness and in the abundance of several fish along the axis of “blind caves” (with a single entrance), as already observed for sessile benthos and plankton assemblages; (2) shallow marine caves of the Salento Peninsula could exert the role of refuge and/or nursery for some littoral fish species during the adult and/or juvenile stages of their life histories.

Temporal Dynamics and Biomass Partitioning in Three Adriatic Seagrass Species: Posidonia oceanica, Cymodocea nodosa, Zostera marina - Paolo Guidetti; Maurizio Lorenti; Maria Cristina Buia; Lucia Mazzella (Marine Ecology, 2002)
The temporal dynamics of three seagrasses, Posidonia oceanica, Cymodocea nodosa and Zostera marina , was studied in different areas of the Adriatic Sea by analysing phenological parameters and biomass trends in different compartments of seagrass systems. For this purpose, samplings were conducted in 1997 once per season at each station, Otranto (southern Adriatic Sea) and Grado (northern Adriatic Sea). Structural parameters and biomass of plant compartments differed among seagrasses both in absolute values and in seasonal variability. P. oceanica was the largest plant, showing the highest number of leaves per shoot, highest leaf surface, Leaf Area Index and shoot weight. Z. marina was intermediate in size and had the longest leaves, whereas C. nodosa was the smallest seagrass. P. oceanica accounted for the highest total biomass (mean ± SE: 1895.9 ± 180.2 g DW · m –2 ; CV = coefficient of variation: 19.0 %), considerably more than C. nodosa (mean ± SE: 410.4 ± 88.4 g DW·m –2 ; CV: 43.1 %) and Z. marina (mean ± SE: 312.1 ± 75.1 g DW · m –2 ; CV: 48.1 %), although the two latter species displayed a higher seasonal variability. Similarly, other features, such as shoot density, leaf surface, LAI, shoot weight and relative contributions of above‐ and below‐ground compartments, were less variable across seasons in P. oceanica than in the two other seagrasses, while leaf length showed the highest seasonal fluctuation in P. oceanica . As for biomass partitioning, C. nodosa showed a higher proportion of the below‐ground relative to above‐ground biomass (up to 90 %), with a distinct seasonality, whereas in P. oceanica the proportion of below‐ground biomass (around 80 %) was fairly constant during the year. We infer that in P. oceanica the seasonal forcing is probably buffered by the availability of internal resources stored permanently during the year in the below‐ground. In C. nodosa and Z. marina , instead, growth processes seem to be amplified by a greater influence of environmental factors.